The Effects of Indirect and Direct Modulation of Endocannabinoid System Function on Anxiety-Related Behavior in Mice Assessed in the Elevated Plus Maze Test - Marta Kruk-Slomka; Agnieszka Dzik; Grazyna Biala (Molecules)
Background: The endocannabinoid system (ECS) is one of the most important systems modulating functions in the body. The ECS, via cannabinoid (CB: CB1 and CB2) receptors, endocannabinoids occurring in the brain (e.g., anandamide (AEA) and 2-arachidonoylglycerol (2-AG)) and enzymes degrading endocannabinoids in the brain (fatty-acid amide hydrolase (FAAH) and monoacylglycerol lipase (MAGL)), plays a key role in the regulation of mood and anxiety. However, the effects of cannabinoid compounds on anxiety-related responses are complex and yield mixed results depending on the type of pharmacological manipulation (direct or indirect) of functions of the ECS, as well as the kinds of cannabinoids, dosage and procedure. Methods: The aim of this study was to determine and compare the influence of the direct (via CB receptors ligands) and indirect (via inhibition of enzymes degrading endocannabinoids in the brain) pharmacological modulation of ECS function on anxiety-like responses in mice in the elevated plus maze (EPM) test. For this purpose, in the first step of the experiments, we used selected ligands of CB1, CB1/CB2 and CB2 receptors to assess which types of CB receptors are involved in anxiety-related responses in mice. Next, we used inhibitors of FAAH (which breaks down AEA) or MAGL (which breaks down 2-AG) to assess which endocannabinoid is more responsible for anxiety-related behavior in mice. Results: The results of our presented research showed that an acute administration of CB1 receptor agonist oleamide (5–20 mg/kg) had no influence on anxiety-related responses and CB1 receptor antagonist AM 251 (0.25–3 mg/kg) had anxiogenic effects in the EPM test in mice. In turn, an acute administration of mixed CB1/CB2 receptor agonist WIN55,212-2 used at a dose of 1 mg/kg had an anxiolytic effect observed in mice in the EPM test. What is of interest is that both the acute administration of a CB2 receptor agonist (JWH 133 at the doses of 1 and 2 mg/kg) and antagonist (AM 630 at the doses of 0.5–2 mg/kg) had anxiogenic effects in this procedure. Moreover, we revealed that an acute administration of only FAAH inhibitor URB 597 (0.3 mg/kg) had an anxiolytic effect, while MAGL inhibitor JZL 184 (at any used doses (2–40 mg/kg)) after an acute injection had no influence on anxiety behavior in mice, as observed in the EPM test. Conclusions: In our experiments, we confirmed the clearly significant involvement of the ECS in anxiety-related responses. In particular, the pharmacological indirect manipulation of ECS functions is able to elicit promising anxiolytic effects. Therefore, the ECS could be a potential target for novel anxiolytic drugs; however, further studies are needed.